2021
DOI: 10.3390/mi12101172
|View full text |Cite
|
Sign up to set email alerts
|

Extending Single Cell Bioprinting from Femtosecond to Picosecond Laser Pulse Durations

Abstract: Femtosecond laser pulses have been successfully used for film-free single-cell bioprinting, enabling precise and efficient selection and positioning of individual mammalian cells from a complex cell mixture (based on morphology or fluorescence) onto a 2D target substrate or a 3D pre-processed scaffold. In order to evaluate the effects of higher pulse durations on the bioprinting process, we investigated cavitation bubble and jet dynamics in the femto- and picosecond regime. By increasing the laser pulse durati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…LIFT has attracted huge attention as bioprinting technique as well, and in the last 20 years, several works have demonstrated applications of 2D and 3D printing of biomolecules and living cells both for in vitro and in vivo approaches [ 52 - 61 ] , including single cell isolation [ 46 , 47 ] and using different laser pulse duration regimes [ 62 ] . In addition, it has been extensively shown that LIFT is one of the bioprinting techniques with the highest cell viability, even better than the widely applied extrusion or inkjet printing methods.…”
Section: Lasers In Ctcs Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…LIFT has attracted huge attention as bioprinting technique as well, and in the last 20 years, several works have demonstrated applications of 2D and 3D printing of biomolecules and living cells both for in vitro and in vivo approaches [ 52 - 61 ] , including single cell isolation [ 46 , 47 ] and using different laser pulse duration regimes [ 62 ] . In addition, it has been extensively shown that LIFT is one of the bioprinting techniques with the highest cell viability, even better than the widely applied extrusion or inkjet printing methods.…”
Section: Lasers In Ctcs Researchmentioning
confidence: 99%
“…In our approach, described in detail in the Methods section, we used a donor structure made with a commercial polyimide film with a thickness of 30 μm. The main advantage of using thick polyimide films is its high absorption in the UV range, efficiently absorbing the laser beam and avoiding direct cell irradiation or even heating of the liquid sample [ 62 , 69 , 73 ] . On the other hand, the use of polyimide presents other advantages: the material is partially transparent to the visible light so fluorescence-vision and techniques for cell recognition and selection can be used, even in a compact optical arrangement in which fluorescence and vision arrangements share the same optical path that the laser beam used to produce the liquid transfer [ 73 ] .…”
Section: Lasers In Ctcs Researchmentioning
confidence: 99%
“…[ 120 ] The effect of laser pulse duration on cell viability has been investigated, by delivering less energy by extending from femtosecond (600 fs) to picosecond (14.1 ps). [ 197 ] When using optimized conditions, a cell‐survival rate post‐transfer of >95% was achieved across the entire pulse duration range. [ 197 ] A similar effect is seen with light‐based 3D bioprinting; however, UV light can cause harmful effects (mutagenic, carcinogenic) which can damage cells and affect cell viability.…”
Section: Bioprinting For Bone Tissue Engineeringmentioning
confidence: 99%
“…[ 197 ] When using optimized conditions, a cell‐survival rate post‐transfer of >95% was achieved across the entire pulse duration range. [ 197 ] A similar effect is seen with light‐based 3D bioprinting; however, UV light can cause harmful effects (mutagenic, carcinogenic) which can damage cells and affect cell viability. [ 198,199 ] Therefore, there is a drive toward developing visible light‐based 3D bioprinting techniques instead.…”
Section: Bioprinting For Bone Tissue Engineeringmentioning
confidence: 99%
“…Absorption of the laser pulse in this case occurs only in the microscopic area of laser beam focusing point. Therefore, radiation can be introduced into the hydrogel in different ways: from below through a transparent gel layer (jets and drops fly out upwards) [15][16][17], and from above through the air medium (jets and drops fly out upwards) [18][19][20]. The disadvantages of using ultrashort laser pulses for bioprinting include the high complexity and cost of the femtosecond laser system, the difficulty of precise focusing, and the ultrahigh pressure and temperature jumps that occur during optical breakdown.…”
Section: Introductionmentioning
confidence: 99%